Balloon Angioplasty as a Modality to Treat Children with Pulmonary Stenosis Secondary to Complex Congenital Heart Diseases - Yan Gu (Chinese Medical Journal, 2017)
Background: Pulmonary stenosis is common in children with complex congenital heart diseases. Proper management of this problem, especially postoperatively, is still controversial. This study was designed to assess the rate and determinants of success or failure of balloon angioplasty for such lesions. Methods: Clinical and hemodynamic data from 40 pediatric patients (24 boys and 16 girls) with complex congenital heart diseases who underwent balloon angioplasty were reviewed retrospectively from January 2012 to December 2016. Patients were divided into four groups according to the site of stenosis, which included pulmonary valve stenosis (PVS), valved conduit stenosis, pulmonary artery stenosis (PAS), and supravalvular pulmonary stenosis (SVPS). Success rates were calculated according to defined criteria for initial success and favorable clinical impacts, and comparison between the successful subgroup and the unsuccessful subgroups was analyzed. Results: Grouped by the site of stenosis, initial success rates varied from 40.0% to 52.4% with the greatest success being seen in the PVS group, followed by the PAS group and SVPS group. In the PVS group and the PAS group, there was no statistical difference among age at dilation, postoperative interval, balloon/stenosis ratio, or pressure gradient predilation between the successful and the unsuccessful subgroups. Favorable clinical impacts included success rates of balloon angioplasty in the SVPS group, which was best (100%), followed by the PVS group (90.9%) and the PAS group (85.7%). There were a total of two transient complications (5.0%). Conclusions: Balloon angioplasty was proven to be a safe and useful modality in children with complex congenital heart diseases and postoperative pulmonary stenosis, which should be the initial therapeutic modality in selected patients.